ANALISIS MANAJEMEN KEUANGAN KELUARGA PADA GURU SMAN 1 BATU AMPAR KABUPATEN KUBU RAYA - Selpawati, Rini; Ulfah, Maria; Kuswanti, Heni (Universitas Tanjungpura, 2023)
This research aims to determine the financial planning, implementation, and evaluation of the family finances of teachers at SMAN 1 Batu Ampar, Kubu Raya Regency. The method used in this research is a case study method with a qualitative approach. In this research, the researcher acts as the main research instrument. Researchers also used recording equipment and interview questions. Data analysis activities by means of data reduction, data display, and data conclusion drawing or verification Research results The majority of respondents have not made detailed and systematic financial plans, although some of them said that they have taken care of family needs and routine expenditure items. Respondent families also do not pay much attention to long-term investments, except for two respondents who own houses and land. The majority of respondents have managed their finances by having planned financial obligation installments and saving regularly. Regarding the financial evaluation aspect, it can be concluded that not all teachers record the financial activities carried out. not using a technological recording system and not following the economic view in recording family finances